Starch and flour extraction and nutrient composition of tuber in seven cassava accessions (Journal of the Bangladesh Agricultural University, 2013)
Cassava (Manihot esculenta Crantz) roots (tubers) are used as staple food. Starch extracted from tubers is widely utilized as raw materials in industries. Dry matter (DM) content, starch and flour extraction and proximate composition were investigated in seven cassava accessions (Coc-A1, Kh-A2, Cow-A3, Sa-A4, Me-A5, Va-A6 and Sy-A8.) in 2010- 2011. Leaf DM varied from 20.51% in Me-A5 to 29.01% in Sy-A8; that of stem from 27.24% in Va-A6 to 32.10% (average of Sy-A8, Me-A5 and Sa-A4); and that of tuber from 37.30% in Kh-A2 to 45.26% in Sy-A8. Starch was extracted by blending chopped tuber followed by decantation. Tubers were sliced, sun dried and milled into flour. Tuber starch content (fresh wt. basis) varied between 15.04% in Sy-A8 and 24.97% (average of Coc-A1 and Me-A5); that of peel from 4.54% in Va-A6 to 5.85% in Coc-A1. Crude protein varied from 1.80% (average of Kh-A2, Cow-A3 and Sy-A8) to 4.53% in Va-A6. Crude fiber content varied from 1.95% (average of Sa-A4 and Coc-A1) to 4.27% in Cow-A3. Cyanogens present in cassava plant escape as hydrogen cyanide (HCN) during harvesting and processing. Variation for HCN existed and it was 140.95 mg/kg fresh tuber (average of Sy-A8 and Coc-A1) to 546.0 mg/kg fresh tuber in Va-A6. There was no detectable HCN in the extracted flour and starch. It may be concluded that genetic variation for DM, starch, protein and HCN existed in seven cassava accessions, and Coc-A1 may be a better one due to its lower HCN, higher DM and starch content. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14698 J. Bangladesh Agril. Univ. 10(2): 217-222, 2012